1995
DOI: 10.21273/hortsci.30.7.1382
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Water Rates for Subsurface Trickle-irrigated Collard, Mustard, and Spinach

Abstract: Three field experiments using subsurface trickle irrigation with various rates of target soil water tension (SWT) and N rates were conducted in southern Arizona during 1990–93. The experiments were conducted with collard (Brassica oleracea L. Acephela Group cv. Vates), mustard [Brassica juncea (L.) Czerniak cv. Southern Giant], and spinach (Spinacea oleracea L. cv. Indian Summer). The interactive effects of water and N tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Similar trends were observed on root length, root diameter and root yield. Similar results were recorded by Feigin et al (1982), Thompson and Doerge, (1995), Zebarth et al (1995), Thompson et al (2000), Ghali et al (2004) and Ouda,soheir (2006).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar trends were observed on root length, root diameter and root yield. Similar results were recorded by Feigin et al (1982), Thompson and Doerge, (1995), Zebarth et al (1995), Thompson et al (2000), Ghali et al (2004) and Ouda,soheir (2006).…”
Section: Resultssupporting
confidence: 87%
“…Regarding the effect of N fertilizers application and water supply methods (fertigation), Feigin et al (1982) and Thompson and Doerge (1995) reported that three qualities are necessary for efficient fertilization through irrigation, they are: (1) irrigation water must contain the needed nutrients in forms available to plants or in forms readily converted to available, forms; (2) water must be uniformly distributed and (3) application of water must be done so that plants are not burned and irrigation lines, emitters or orifices are not plugged. Cortez et al (2000) stated that this method (fertigation) produces good results, including higher overall agricultural yield.…”
Section: Introductionmentioning
confidence: 99%
“…Cole crops grown under arid conditions in Arizona with little rainfall respond to low SWT criteria. Irrigation criteria as wet as 6 to 12 kPa are recommended for production on sandy loam in fall-winter in Arizona (Thompson and Doerge, 1995;Thompson et al, 2000aThompson et al, , 2000bThompson et al, , 2002aThompson et al, , 2002b. Broccoli grown in the spring at Agassiz, British Columbia, Canada, showed little difference in yields when grown at 20 or 30 kPa all season compared with 50 kPa during plant development followed by 20 kPa during head formation (Maurer, 1976).…”
Section: Crops Respond Differently To Soil Water Tensionmentioning
confidence: 99%
“…Generally, they found that spinach yield and its components were higher at either 100% or 75% Etc rates of irrigation. On the other hand, Thompson and Doerge (1995) found that excessive irrigation resulted in lower yield of spinach. Also, Sanchez (2000) and Karam et al (2002) stated that water deficit reduced leaves number, leaf area and dry matter content characters in spinach plants.…”
Section: Introductionmentioning
confidence: 99%